Кошелек или жизнь?: [повести] / Марина Серова - Серова Марина Сергеевна (Русский бестселлер, 2002)
Экземпляры: Ф. 13 (20190924) / Инвентарный номер: 47177 / Цена: 20.00 / Сис.шифр: Р2 / Авт.знак: С 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44